Catalytic Performance of Ceria-supported Cobalt Catalyst for CO-rich Hydrogen Production from Dry Reforming of Methane - Ayodele, Bamidele V.; Khan, Maksudur R.; Cheng, C. K. (Elsevier, 2016)

(untitled)
Dry reforming of methane was studied over ceria-supported cobalt (20wt%) catalyst prepared via wet-impregnation method. The synthesized catalyst was characterized using thermogravimetric analysis (TGA), X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), energy dispersive X-ray spectroscopy (EDX), N2 physisorption and Fourier transform infrared spectroscopy (FTIR). The catalytic methane dry reforming was carried out over the 20wt%Co/80wt%CeO2 catalyst in a fixed-bed reactor. The experiment was performed at atmospheric condition with time-on-stream (TOS) of 4 h, reaction temperatures of 923–1023 K, and CH4:CO2 feed ratios of 0.1–1.0. The XRD pattern showed good dispersion of the cobalt metal on the support. This was corroborated by the FESEM-EDX and FTIR spectrum. The N2 physisorption revealed that the BET specific surface area of the calcined catalyst was more than double the ceria support. The conversions of CH4 and CO2, respectively, as well as the H2 and CO yield, were found to increase with reaction temperature and CH4:CO2 feed ratios. The highest conversions for both CO2 and CH4 were 87.6% and 79.5%, respectively, at 1023 K. Moreover, highest yield of 40% was obtained for CO while that of H2 was 37.6%. Syngas ratio of 0.99 was obtained at a feed ratio of 0.9, which has further cemented the suitability of methane dry reforming over ceria-supported cobalt catalyst for production of syngas meant for Fischer–Tropsch synthesis.